A Window of Opportunity : The Managing Director's Global Policy Agenda. (Policy Papers; Policy Paper, 2017)
The global recovery continues. Although it is not yet complete, the more favorable conjuncture offers an opportunity to tackle key policy challenges to stave off medium-term downside risks, rebuild buffers, and raise potential output. Countries should undertake well-sequenced reforms to increase productivity, improve governance, and reduce policy uncertainty and future risks. Reforms should also aim to harness the benefits of technology and economic integration and ensure that they are widely shared. Tackling challenges to the global economy continues to require cooperation and joint action across the membership. The Fund will assist members through tailored policy advice and capacity development, and stands ready to provide financial assistance to support adjustment programs.